THE IMPACT OF SENSORY MARKETING ON CUSTOMER SATISFACTION AND REPURCHASE INTENTION (STUDY CASE IN GRAND KARTIKA HOTEL RESTAURANT IN PONTIANAK) - B12112024, NURUL DILAH PALUPI (Jurnal Manajemen Update, 2018)
The aim of this research is to analyze the impact of sensory marketing dimensions on customer satisfaction and repurchase intention in Grand Kartika Hotel Restaurant in Pontianak. The data is obtained from distributing the questionnaires to the restaurant customers based on the convenience sampling method, and the data is evaluated by Structural Equation Model (SEM).According to the analysis, the result shows that Hypothesis 1 is accepted where there is a positive relationship and significant impact of sight sense on customer satisfaction. Hypothesis 2 is accepted where there is a positive relationship and significant impact of sound sense on customer satisfaction. Hypothesis 3 is rejected where there is a positive relationship but not significant impact between smell sense and customer satisfaction. Hypothesis 4 is accepted where there is a positive relationship and significant impact of taste sense on customer satisfaction. Hypothesis 5 is rejected where there is a positive relationship but not significant impact between touch sense and customer satisfaction. Hypothesis 6 is accepted where there is a positive relationship and significant impact of sight sense on repurchase intention. Hypothesis 7 is accepted where there is a positive relationship and significant impact of sound sense on repurchase intention. Hypothesis 8 is accepted where there is a positive relationship and significant impact of smell sense on repurchase intention. Hypothesis 9 is accepted where there is a positive relationship and significant impact of taste sense on repurchase intention. Hypothesis 10 is rejected where there is a positive relationship but not significant impact between touch sense and repurchase intention. Hypothesis 11 is rejected where there is a significant impact but negative relationship between customer satisfaction and repurchase intention.Keywords: Sensory Marketing, Customer Satisfaction, Repurchase Intention, Restaurant, Structural Equation Model (SEM)REFFERENCESAbdillah, W., & Hartono, J. (2015). Partial Least Square (PLS): Alternatif Structural Equation Modelling (SEM) dalam Penelitian Bisnis. Yogyakarta: Penerbit Andi.Acevedo, C. R., & Fairbanks, V. S. (2017, March). The Effects of Sensory Marketing on Shopping Exerience and on Consumer Decision Making. European Journal of Business and Social Sciences, V, 62.Araci, U. E., Bulut, Z. A., & Kocak, N. (2017, September). The Relation Among Experiential Marketing, Customer Satisfaction, and Behavioral Intention; A Case Study on Food and Beverage Businesses. 369.Baron, R. M., & Kenny, D. A. (1986). The Moderator-Mediator Variable Distinction in Social Psychological Research: Conceptual, Strategic, and Statistical Considerations. Journal of Personality and Social Phychology, 51(6), 1176.BPS. (2016). Statistik Wisatawan Mancanegara Kota Pontianak 2016. Pontianak: Badan Pusat Statistik.BPS. (2016). Tingkat Penghunian Kamar Hotel Kota Pontianak 2016. Pontianak: Badan Pusat Statistik.Chebat, J. C., & Michon, R. (2003). Impact of Ambient Odors on Mall Shoppers' Emotions, Cognition, and Spending: A Test of Competitive Causal Theories. Journal of Business Research, 529.Cooper, D. R., & Emory, C. W. (1996). Metode Penelitian Bisnis. Jakarta: Penerbit Erlangga.Cooper, D. R., & Schindler, P. S. (2014). Business Research Methods. Newyork: McGraw-Hill/Irwin.Czinkota, M. (2015, February 5). Retrieved October 8, 2017, from MichaelCzinkota.com: http://www.michaelczinkota.com/2015/02/oreo-global-brand-adapted-local-tastes/Elangovan, & Padma. (2017, February). Impact of Multisensory Marketing on Consumer Behavior in Restaurant. International Journal of Business and Management Invention, VI(2), 7.Hadiwinata, A. (2017, 12 13). Number of Customer of Grand Kartika Hotel in Pontianak within 5 Years. (N. D. Palupi, Interviewer)Hadiwinata, A. (2017, 12 13). Restaurant's Competitive Advantages to Compete in Attracting Customers. (N. D. Palupi, Interviewer)Hinestroza, N., & James, P. (n.d.). The Effect of Sensory Marketing on The Implementation of Fast-Food Marketing Campaigns. Journal of Management and Marketing Research.Hussain, S. (2014). The Impact of Sensory Branding (Five Senses) on Consumer: A Case Study on KFC (Kentucky Fried Chicken). International Journal of Research in Business Management, II(5), 49.indahnesia.com. (2009, December 2). Indahnesia. Retrieved January 31, 2018, from indahnesia.com: indahnesia.com/indonesia/KABKAP/the_kapuas_river.phpKerin, R. A., Hartly, S. W., & Rudelius, W. (2009). Marketing. Newyork: McGraw-Hill Irwin.Kotler, P., & Armstrong, G. (2011). Principles of Marketing. Prentice Hall.Kotler, P., & Armstrong, G. (2014). Principles of Marketing (15th ed.). Harlow: Pearson Education Limited.Kotler, P., & Armstrong, G. (2014). Principles of Marketing (15 ed.). Harlow, England: Pearson Education Limited.Kotler, P., & Keller, K. L. (2012). Marketing Management (14 ed.). Harlow, England: Pearson Education Limited.Krishna, A. (2010). Sensory Marketing: Research on The Sensuality of Products. New York: Routledge.Kuncoro, M. (2009). Metode Riset untuk Bisnis & Ekonomi. Jogjakarta: Penerbit Erlangga.Level, D. P.-N. (2015, July 3). Perkembangan Demograi dan Perekonomian Kota Pontianak. Retrieved January 31, 2018, from bappeda.pontianakkota.go.id: bappeda.pontianakkota.go.id/berita-31-perkembangan-demografi-dan-perekonomian-kota-pontianak.htmlLovelock, C., & Wirtz, J. (2012). Service Marketing: People, Technology, Strategy (7th ed.). Harlow: Pearson Education Limited.Madjid, R. (2014, October). The Influence Store Atmosphere Towards Customer Emotions and Purchase Decisions. International Journal of Humanities and Social Science Invention, III(10), 12.Mehrnaz, S., Mobarakabadi, H., & Hamidi, K. (2015). Sensory Marketing and Consumer Buying Behavior. Advanced Social Humanities and Management, IV, 100-104.Muhammad, F., Suharyono, & Alfisyahr, R. (2017). Pengaruh Sensory Marketing terhadap Kepuasan Konsumen dan Repurchase Intention. Jurnal Administrasi Bisnis, 94.Muhammad, F., Suharyono, & Alfisyahr, R. (2017). Pengaruh Sensory Marketing terhadap Kepuasan Konsumen dan Repurchase Intention: Survei pada Konsumen Nomu 9 Bites & Beverages di Kota Malang. Jurnal Administrasi Bisnis, 90.Muhammad, F., Suharyono, & Alfisyahr, R. (2017). Pengaruh Sensory Marketing terhadap Kepuasan Konsumen dan Repurchase Intention: Survei pada Konsumen Nomu 9 Bites and Beverages di Kota Malang. Jurnal Administrasi Bisnis, 93.Noor, J. (2015). Metodologi Penelitian: Skripsi, Tesis, Disertasi, dan Karya Ilmiah (5th ed.). Jakarta: Prenadamedia Group.Nugraha, M. E., & Setiyorini, D. (2013). Analisis Faktor-Faktor Sensory Marketing pada Maskapai Penerbangan (Survei pada Wisatawan Mancanegara yang Pernah Menggunakan The Worlds 4 Star Airline di Bandara International Soekarno-Hatta). Tourism and Hospitality Essentials Journal, 530.Petzer, D., & Mackay, N. (2014). Dining Atmosphere and Food and Service Quality as Predictors of Customer Satisfaction at Sit-Down Restaurants. African Journal of Hospitality, Tourism and Leisure, III(2), 5.Prasetyo, B., & Jannah, L. M. ( 2012). Metode Penelitian Kuantitatif (7th ed.). Jakarta: Rajagrafindo Persada.Randhir, R., Latasha, K., Tooraivaen, p., & Monishan, B. (2016, April). Analyzing The Impact of Sensory Marketing on Consumers. Journal of US-China Public Administration, XIII(4), 285.Randhir, R., Latasha, K., Tooraiven, P., & Monishan, B. (2016). Analyzing the Impact of Sensory Marketing on Consumers: A Case Study of KFC. Journal of US - China Public Administration, XIII, 279.Randhir, R., Latasha, K., Tooraiven, P., & Monishan, B. (2016, April). Analyzing The Impact of Sensory Markting on Consumers: A Case Study of KFC. Journal of US-China Public Administration, XIII(4), 286.Razi, F. F., & Lajevardi, M. (2016). Sense Marketing, Experiential Marketing, Customer Satisfactionand Repurchase Intention. Journal of Marketing and Consumer Research, XXI, 69.Sangadji, E. M., & Sopiah. (2010). Metodologi Penelitian: Pendekatan Praktis dalam Penelitian. Yogyakarta: Penerbit Andi.Sangadji, E. M., & Sopiah. (2013). Perilaku Konsumen: Pendekatan Praktis disertai Himpunan Jurnal Penelitian. Yogyakarta: Penerbit Andi.Sayadi, M., Mobarakabadi, H., & Hamidi, K. (2015). Sensory Marketing and Consumer Buying Behavior. Advanced Social Humanities and Management, 101.Sekaran, U. (2003). Research Methods for Business. John Wiley & Son.Senduk, D. C., Saerang, D. P., & Lambey, L. (2016). The Influence of Restaurant Ambience and Service Quality on Customer Satisfaction at PondokHijau Restaurant Manado. Jurnal Berkala Ilmiah Efisiensi, XVI(3), 241.Sholihin, M., & Ratmono, D. (2013). Analisis SEM-PLS dengan WrapPLS 3.0. Yogyakarta: Penerbit Andi.Siregar, S. (2014). Statistik Parametrik untuk Penelitian Kuantitatif. Jakarta: Bumi Aksara.Solomon, M. R. (2012). Consumer Behavior (10 ed.). New Jersey: Prentice Hall.Solomon, M. R. (2012). Consumer Behavior: Buying, Having, and Being (10 ed.). Harlow, England: Pearson Education Limited.Suharso, P. (2012). Metode Penelitian Kuantitatif untuk Bisnis: Pendekatan Filosofi dan Praktis (3rd ed.). Jakarta: Indeks.Suliyanto. (2014). Statistika Non-Parametrik dalam Aplikasi Penelitian. Yogyakarta: Penerbit Andi.Supriyanto. (2009). Metodologi Riset Bisnis. Jakarta: Malta Printindo.Suryawan, S., & Dharmayanti, D. (2013). Analisa Hubungan antara Experiential Marketing, Customer Satisfaction dan Customer Loyalty Cafe Nona Manis Grand City Mall Surabaya. Jurnal Manajemen Pemasaran, 5.Tetanoe, V. R., & Darmayanti, D. (2014). Pengaruh Experiential Marketing terhadap Pembelian Ulang Dengan Kepuasan Pelanggan sebagai Variable Intervening di Breadtalk Surabaya Town Square . Jurnal Manajemen Pemasaran Petra, II(1), 5.Tetanoe, V. R., & Dharmayanti, D. (2014). Pengaruh Experiential Marketing terhadap Pembelian Ulang dengan Kepuasan Pelanggan sebagai Variable Intervening di Breadtalk Surabaya Town Square. Jurnal Manajemen Pemasaran Petra, 9.Yulianti, N. M., Suprapti, N. W., & Yasa, N. N. (2014). Pengaruh Citra Toko            Terhadap         Kepuasan Pelanggan dan Niat Beli Ulang Pada Circle K di Kota            Denpasar. Jurnal         Manajemen Strategi Bisnis dan Kewirausahaan , 38.